Hukuman Mati Bagi Koruptor Pada Saat Keadaan Tertentu (Pandemi COVID-19) Perspektif Hukum Nasional dan Hukum Islam - Daipon, Dahyul (Al-Manahij: Jurnal Kajian Hukum Islam, 2021)
The current condition of the Covid-19 pandemic is a time where almost everyone feels social and economic difficulties. Communities whose regions apply restrictions/quarantines are highly dependent on assistance from the government. This paper is a study and analysis of one question how the death penalty can be applied to perpetrators of corruption during the Covid-19 outbreak or pandemic. In the criminal law that applies in Indonesia, the death penalty for perpetrators of criminal acts of corruption is contained in Article 2 paragraph 2 of Law no. 31 of 1999 concerning the Eradication of Corruption Crimes. Meanwhile, in Islamic law, corruption is categorized as jarimah ta'zir. The results of this study conclude that during a pandemic, the death penalty can be applied to corruptors in accordance with the provisions of Article 2 of the Anti-Corruption Law and the provisions of Islamic criminal law as jarimah ta'zir. There are fundamental differences in the application of the death penalty for corruptors according to positive law and Islamic criminal law, especially with regard to the conditions required for the imposition of the death penalty. Even though this seems cruel according to human rights supporters, this needs to be a concern for all law enforcers so that they can carry out strict law enforcement against perpetrators of corruption crimes during the pandemic.